Social capital in the context of housing and neighbourhood management: A preliminary literature review - Richard Lang; Dietmar Roessl (European Regional Science Association (ERSA), 2010)
This paper provides a systematic literature overview of existing research on social capital in relation to housing and neighbourhood management. A growing body of research documents the significance of social capital for the social cohesion and well-being of neighbourhoods. Thus, in recent years, social capital has become a key concept for both, practitioners and academics dealing with issues of housing and neighbourhood management. However, as a result of its widespread use, social capital has also developed into a rather heuristic concept, generating controversy about its conceptualisation and measurement. Consequently, published articles show a high level of heterogeneity in their social capital approaches and thus, raise the demand for a review of current research in housing and neighbourhood management. Applying the method of systematic literature review, this article first identifies different schools of social capital research in the current research on housing and neighbourhood management. In a second step, theoretical as well as empirical contributions, within these research streams, are analysed and evaluated with regard to content and methodology. Finally, the paper aims to identify possible benefits and pitfalls of the different conceptualisations of social capital when studying housing areas and drawing implications for their management. Our findings highlight a lack of consensus on what social capital is, and how it should be defined in the context of housing and neighbourhood management. From the review, it is evident that researchers primarily focus on solidarity norms and patterns of social and political participation on the neighbourhood level, thus, treating social capital as a collective asset. However, extending the concept from its theoretical roots in social networks can lead to major conceptualisation and measurement problems. Thus, without clarifying the relationship between variables on the individual and collective level, the usefulness of social capital as an analytical concept for the study of housing areas is likely to be limited.
Keywords: 330